The Politics of Virtue for Capital Accumulation - Arif Novianto; Kurnia Cahyaningrum Effendi; Yuyun Purbokusumo (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
Discourses about Corporate Social Responsibility (CSR) are generally understood as goodwill and social virtue. This research with a CSR Indocement case study in the Pati District found something different in the study in areas that have not been affected by and in the process of expansion from PT SMS (a subsidiary of PT Indocement Tunggal Prakarsa). CSR Indocement, which has been run in Pati since 2012, is not based on a business ethic or corporate social virtue model. With political economy analysis, we found that 1) CSR Indocement runs in Pati as an effort to expedite the expansion of their capital which has strong resistance from the community rejecting the cement factory; 2) CSR Indocement for the last five years in Pati, nearly 90 programs that have been attempted none have been able to empower the community. These efforts were influenced by two things: 1) In carrying out its program CSR Indocement brought the program to the village elites. 2) CSR Indocement's initial goal for Pati was to build a consensus to give a red carpet for capital expansion so that the goal of empowerment is not paramount.